Brexit and new autochthonic politics of belonging. Issue 2 (4th May 2018) - Cassidy, Kathryn; Innocenti, Perla; Bürkner, Hans-Joachim
ABSTRACT: The outcome of the 2016 European Union membership referendum is re-shaping the United Kingdom's relationship with the EU through shifting geopolitical positioning(s) and the (re)introduction of barriers and boundaries and also challenging British and EU citizens to revise their everyday sense of belonging. Accordingly, Brexit incorporates emergent and contested political projects of belonging, determining anew who belongs in a post-EU Britain. This paper discusses research directions focusing on the construction of political and everyday senses of belonging implied by public debates on Brexit, and critically examines the shifts in attitude towards received citizenship and different degrees of social exclusion.